In vitro and in vivo efficacy studies of an engineered endolysin targeting Gram-negative pathogens - Hong, Hye Won; Jang, Jaeyeon; Kim, Young Deuk; Jeong, Tae Hwan; Lee, Dogeun; Park, Kyungah; Kim, Min Soo; Yoon, In Soo; Song, Miryoung; Seo, Min Duk; Yoon, Hyunjin; Lim, Daejin; et al. (International Journal of Biological Macromolecules, 2025)
Endolysins have drawn considerable attention as viable modalities for antibiotic use. The most significant obstacle for Gram-negative targeting endolysins is the presence of the outer membrane barrier. A heterologously expressed endolysin encoded by bacteriophage PBPA90 infecting Pseudomonas aeruginosa exhibited intrinsic antibacterial activity against P. aeruginosa. The antibacterial efficacy was improved by substituting 15 amino acids and by fusing cecropin A to the N-terminus. The resulting engineered endolysin, LNT103, demonstrated strong antibacterial activity, with minimum inhibitory concentrations as low as 4 μg/ml, against various Gram-negative pathogens in addition to P. aeruginosa, including Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae, Klebsiella aerogenes, and Enterobacter cloacae. The engineered endolysin rendered both the outer and the inner bacterial membranes permeable. It exhibited a synergistic effect with colistin, and additive effects with carbapenem antibiotics. Bacterial resistance development to LNT103 was none to minimal in vitro. Its in vivo efficacy was verified in bacteremia models of mice infected with A. baumannii. The endolysin led to a resensitization of resistant bacteria to meropenem when used in combination in vivo.
Keywords: Acinetobacters; Baumannii; Carbapenem-resistant acinetobacter baumannii; Carbapenems; Engineered endolysin; Gram-negative; Gram-negative pathogens; In-vitro; Mice models; Vivo efficacies; Animals; Anti-Bacterial Agents; Endopeptidases; Gram-Negative Bacteria; Gram-Negative Bacterial Infections; Mice; Microbial Sensitivity Tests; Protein Engineering; Carbapenem-resistant Acinetobacter baumannii; Engineered endolysin; Gram-negative; Mouse model